2021
DOI: 10.1038/s41598-021-82244-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anticancer activity of hydrogen sulfide and nitric oxide alongside nickel nanoparticle and novel mutations in their genes in CRC patients

Abstract: This study was carried out to assess the impact of nickel nanoparticles (NiNPs) as well as scorpion venom on colorectal cancer (CRC) cells in the presence and/or absence of 5-fluorouracil (5-FU), hydrogen sulfide (H2S), and nitric oxide (NO) donors and to determine alterations in endothelial NO synthase (eNOS) and cystathionine γ-lyase (CSE) enzyme-producing genes in CRC patients. The IC50 of both H2S and NO donors, along with NiNPs, were determined. The CRC cells were treated for 24hrs, and the cytotoxic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Metallic nanoparticles also have excellent potential to inhibit DPPH. The results obtained in our study are in line with many studies in which the mutual effect has been monitored to increase the antioxidant capacities between herbs and metallic salts against DPPH [13][14][15][16]. In general, metallic nanoparticles display remarkable and extraordinary antioxidant impacts, among which the antioxidant effects of FeNPs have been well-documented.…”
Section: Antioxidant Properties Of Fenps Against Dpphsupporting
confidence: 89%
See 3 more Smart Citations
“…Metallic nanoparticles also have excellent potential to inhibit DPPH. The results obtained in our study are in line with many studies in which the mutual effect has been monitored to increase the antioxidant capacities between herbs and metallic salts against DPPH [13][14][15][16]. In general, metallic nanoparticles display remarkable and extraordinary antioxidant impacts, among which the antioxidant effects of FeNPs have been well-documented.…”
Section: Antioxidant Properties Of Fenps Against Dpphsupporting
confidence: 89%
“…More importantly, laboratory evidence has shown that antioxidants can highly prevent cancer [13][14][15][16].The IC50 of BHT and FeNPs were 91 and 132 µg/mL, respectively (Figure 4; Table 1).…”
Section: Antioxidant Properties Of Fenps Against Dpphmentioning
confidence: 94%
See 2 more Smart Citations
“…It is clear that H 2 S, similar to other endogenous gases, has now been identified as a gasotransmitter ( 77 ). It was initially regarded as highly poisonous in the environment; however, this perception has changed as a growing number of studies have illustrated H 2 S as a cytoprotective and cardioprotective agent ( 78 , 79 ). Fig.…”
Section: Gasotransmittersmentioning
confidence: 99%